2020
DOI: 10.1002/ejhf.1735
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk and atrial fibrillation in patients with heart failure

Abstract: Aims To study the association between an atrial fibrillation (AF) genetic risk score with prevalent AF and all‐cause mortality in patients with heart failure. Methods and results An AF genetic risk score was calculated in 3759 European ancestry individuals (1783 with sinus rhythm, 1976 with AF) from the BIOlogy Study to TAilored Treatment in Chronic Heart Failure (BIOSTAT‐CHF) by summing 97 single nucleotide polymorphism (SNP) alleles (ranging from 0–2) weighted by the natural logarithm of the relative SNP ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
0
14
0
1
Order By: Relevance
“…section). 23,64,65 These improvements contributed to the accuracy of risk prediction in 2 ways. First, they improve the accuracy of the prediction of AF in the absence of clinical risk factors (eg, early-onset AF).…”
Section: Atrial Fibrillationmentioning
confidence: 99%
See 1 more Smart Citation
“…section). 23,64,65 These improvements contributed to the accuracy of risk prediction in 2 ways. First, they improve the accuracy of the prediction of AF in the absence of clinical risk factors (eg, early-onset AF).…”
Section: Atrial Fibrillationmentioning
confidence: 99%
“…shown incremental predictive capabilities in addition to clinical risk factors. 20,23,[64][65][66][67][68][69] Proposed utility has been to refine the identification of individuals meriting close surveillance for AF development. 4.…”
Section: Atrial Fibrillation: Prss For Af Have Consistentlymentioning
confidence: 99%
“…Atrial fibrillation (AF) is the most common arrhythmia in heart failure (HF) with a prevalence between 20-60% depending on the type and severity of HF. [1][2][3] Both AF and HF are strongly associated with ageing, share many other clinical risk factors such as obesity and hypertension, and can trigger each other. 2,3 Distinct differences are observed when comparing patients with HF with and without AF.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Both AF and HF are strongly associated with ageing, share many other clinical risk factors such as obesity and hypertension, and can trigger each other. 2,3 Distinct differences are observed when comparing patients with HF with and without AF. We recently showed that patients with AF and HF are older, less often have an ischemic aetiology of HF, and have a distinct biomarker profile as compared with HF patients in sinus rhythm.…”
Section: Introductionmentioning
confidence: 99%
“…В исследовании M. Kloosterman и соавт. среди пациентов, находящихся на гемодиализе, распространенность персистирующей ФП составила 23,4% [1]. По данным метаанализа D. Zimmerman и соавт., ФП обнаружена у 27% пациентов, находящихся на диализе, и у 13,9% пациентов регистрировалась постоянная ФП.…”
Section: Introductionunclassified